PENGARUH MEMBATASI MOBILITAS KERETA API GUNA MENCEGAH COVID-19 DENGAN UJI-T BERPASANGAN (PAIRED SAMPLE T-TEST) - Wella Ayu Sheilliarika; Sri Maryani; Hendi Efendi (Jurusan Matematika FMIPA Universitas Jenderal Soedirman, 2021)
Director General of the World Health Organization (WHO) Tedros Adhanom Ghebreyesus officially announced the coronavirus (COVID-19) as a pandemic, on March 11, 2020. To prevent the spread of coronavirus in Indonesia a Work From Home (WFH) policy, Large-Scale Social Restrictions (PSBB) was made. , as well as limiting the mobility of people from one area to another. One of them is PT Kereta Api Indonesia which directly reduces the number of long-distance train trips. Because of the dangers of the coronavirus and the issuance of government policies, citizens swiftly comply with the policies that have been issued. Therefore, it is necessary to know whether there is an influence on the passenger volume of the economi class Train (KA) before and after the Covid-19. The method used for known data is the Comparative Hypothesis Test. The decision obtained was that there was an influence on the volume of economi class train passengers before and after the Covid-19.